TADALAFIL AS AN AGENT OF PHARMACOLOGICAL PRECONDITIONING IN ISCHEMIC - REPERFUSION BRAIN INJURY - Olga Martynova (Belgorod National Research University, 2017)
Introduction: Ischemic stroke or cerebral infarction is the main pathology among severe forms of vascular lesions of the brain. One of the more effective non-medicamental methods of treatment is pharmacological preconditioning. Pharmacological neuroprotection is one of the treatment areas to reduce the damage in ischemic stroke and other modifications of brain ischemia. Therefore, the development and introduction of new pharmacological agents that can reduce the degree of ischemic-reperfusion injury of the brain, remains one of the major challenges of modern medicine. The most promising to explore, from our point of view, is a PDE-5 inhibitor. Goal: Improving the efficiency of pharmacological cerebroprotective with pharmacological preconditioning of the PDE-5 inhibitor (tadalafil) in comparison with recombinant erythropoietin («Epocrin») and a neuroprotectant "Gliatilin". Materials and methods: In the pilot study used an integrated approach to the study of neuroprotective effects of pharmacological preconditioning in animals with ischemia-reperfusion brain damage in four-vascular total ischemia of the brain. In the complex of methods included evaluation of neurological deficit, behavioral status, level of markers of brain damage S100b and NSE, morphometry. To compare the efficacy of tadalafil (1 mg/kg) in the experiment used recombinant erythropoietin «Epocrin» (50 IU/kg) and the neuroprotectant "Gliatilin" (85.7 mg/kg). Results and discussion: Prophylactic intraperitoneal administration of PDE-5 inhibitor, tadalafil (1 mg/kg) exerted cerebroprotective effect in modeling of ischemia-reperfusion, expressed in reducing the severity of neurological deficit (0.8±0.21 points), compared with the control group (of 2.05±0.49 points); increase in the number of stands at 1.7 times and 2.2 hanging times; not a big increase in overall activity, patterns of movement, maximum speed, total distance increased 1.5 times, decrease rest time by 1.2 times; the reduction in the concentration of damage markers S100b 3.5 times and the NSE in 2 times. A number of distinctive characteristics the morphometric study, as well as a set of symptoms, manifestations of behavioral reactions confirm the fact of cerebroprotective properties of tadalafil in comparison with the control group animals. Conclusions: the conducted research showed cerebroprotective property of an inhibitor of phosphodiesterase type 5, tadalafil. The results of the study clearly indicate the prospects of its use in vascular pathology of the brain.